GOOD CORPORATE GOVERNANCE MECHANISMS IN MEASURING QUALITY OF FINANCIAL STATEMENTS AND TRANSFER INVESTOR LEVELS - Syafrida Hani; Hafsah UMSU (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
ABSTRACTThis study aims to develop a theory of determining the quality of financial statement reports that can increase  investor  confidence  in  financial  information  presented  by management.  This  research would like to find the role of good corporate governance  in improving the quality of financial statements as measured by accounting conservatism and earnings management, then it will be seen how the quality ability of financial statement can influence investor confidence level. The result of the research  did  not  find  the  influence  of corporate  governance  mechanism  on  the  quality of financial statements. However, the simultaneous test results found that corporate governance mechanisms  and  the  quality  of  financial  statements  affect  the  level  of  investor  confidence. Profit management as an indicator of the quality of financial statements negatively affects the level of investor confidence. But accounting conservatism declared no effect on the level of investor confidence. The results of the test with path analysis found that the variables that have a direct influence of the mechanism of good corporate governance is the ownership of the institution, while other variables have no influence either directly or indirectly.